Understanding Chinese MA Students’ Interpersonal Stance of Anticipatory “It” Patterns: Using Corpus Results to Guide Questionnaire and Discourse-Based Interview - Jing Chen; Yi Jiang (SAGE Open)
Anticipatory “it” pattern, which encodes interpersonal stance, plays a crucial role in academic writing. While previous studies have been explored the overuse and the underuse of this pattern among English as a Foreign Language (EFL) learners and published writers, there has been limited exploration of how EFL learners use the anticipatory “it” pattern to express interpersonal stance in their academic writing. This study examines the relationship between Chinese MA students’ perceptions of interpersonal stance and their use of anticipatory “it” patterns in academic writing. Utilizing a self-compiled corpus of Chinese MA theses corpus, supplemented by a questionnaire and discourse-based interviews, this research aims to identify factors influencing students’ motivations to employ this pattern. Applying Hewings and Hewings’ functional typology of interpersonal functions of the “it” clause, the results reveal varying correlations across four categories of interpersonal functions in Chinese MA theses. These findings offer valuable insights into the nuanced relationship between students’ perceptions of interpersonal stance and their use of anticipatory “it” pattern, with implications for teaching and learning academic English writing.